2023
DOI: 10.3350/cmh.2023.0202
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization for hepatocellular carcinoma: 2023 Expert consensus-based practical recommendations of the Korean Liver Cancer Association

Abstract: Transarterial chemoembolization (TACE) was introduced in 1977 with the administration of chemotherapeutic agent to gelatin sponge particles through the hepatic artery in patients with hepatocellular carcinoma (HCC) and was established as conventional TACE using Lipiodol in the 1980s. In the 2000s, drug-eluting beads were developed and applied clinically. Currently, TACE is a commonly used non-surgical treatment modality for patients with HCC who are unsuitable for curative treatment. Considering the vital role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…[24] Additionally, previous studies had demonstrated that the combination of sorafenib with local tumor treatments, such as TACE or EBRT, could achieve superior therapeutic effects in HCC patients with PVTT, compared to sorafenib alone. [25][26][27] A pivotal phase III clinical trial contrasted the efficacy of sorafenib monotherapy (s-m group) with sorafenib plus local treatment (including intra-arterial chemotherapy and radiation therapy, referred to as the s-lrts group) in advanced HCC patients. [28] Among the 290 patients in this trial, those in the s-lrts group experienced both a median PFS of 5.3 months and a median OS of 8.5 months, exceeding the outcomes in the s-m group.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Additionally, previous studies had demonstrated that the combination of sorafenib with local tumor treatments, such as TACE or EBRT, could achieve superior therapeutic effects in HCC patients with PVTT, compared to sorafenib alone. [25][26][27] A pivotal phase III clinical trial contrasted the efficacy of sorafenib monotherapy (s-m group) with sorafenib plus local treatment (including intra-arterial chemotherapy and radiation therapy, referred to as the s-lrts group) in advanced HCC patients. [28] Among the 290 patients in this trial, those in the s-lrts group experienced both a median PFS of 5.3 months and a median OS of 8.5 months, exceeding the outcomes in the s-m group.…”
Section: Discussionmentioning
confidence: 99%
“…TACE is often recommended for patients with large or multiple HCC and is commonly used as a salvage treatment for recurrent cases after radical treatment, as well as an initial treatment for HCC. 10 TACE often leads to postembolisation syndrome, characterised by symptoms such as fever, nausea, vomiting, abdominal pain and liver damage. 10 Moreover, patients undergoing TACE treatment are typically advised to rest.…”
Section: Introductionmentioning
confidence: 99%
“… 10 TACE often leads to postembolisation syndrome, characterised by symptoms such as fever, nausea, vomiting, abdominal pain and liver damage. 10 Moreover, patients undergoing TACE treatment are typically advised to rest. According to Kortebein et al , 11 significant skeletal muscle loss can occur due to 10 days of bed rest.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave ablation, cryoablation, or external radiation therapy may be more effective than radiofrequency ablation when the tumor abutts the large vessels [ 3 ]. Deep-seated tumors in the Spiegel lobe may be challenging for percutaneous ablation but can be easily treated with superselective chemoembolization or radioembolization with cone-beam computed tomography guidance [ 4 ]. A tumor just below the heart may be more suitable for intra-arterial than for percutaneous therapy.…”
mentioning
confidence: 99%